Investigation of the secondary metabolome of fungi from Svalbard island (usage of epigenetic elicitor in fungi chemistry) / Nor Fadhilah Mohammad - Mohammad, Nor Fadhilah (2014)
Eight types of psychrophilic fungi were isolated from Svalvard Island, Norway which is in an extreme low temperature those are A2C2, BlCl, C1C2, DICDl I, DICD12, ElCl and E3CD. These fungi were then undergoing several steps to investigate their secondary metabolites in two different of incubation times as these psychrophilic fungi were capable to grow their secondary metabolites in extreme low temperature. We investigated the secondary metabolites that produced by these fungi in 10°C within two different incubation times of 3 weeks and 5 weeks. These fungi then extracted and the crude extracts were proceeded to HPLC profiling. After comparing each secondary metabolites that were produced by these fungi we found that difference fungi produced their interesting metabolites when grow in low temperature. Further investigation is needed for identification of interesting compound in each secondary metabolites that produced by these fungi.